Implementation and evaluation of “I-Guide,” a pilot near-peer Internal Medicine mentorship program (Canadian Medical Education Journal, 2021)
Implication StatementAn Internal Medicine (IM) specific, near-peer mentorship program was initiated at the University of Ottawa (uOttawa) in 2017. Medical students were paired with IM resident mentors in an effort to improve career decision-making. Additionally, residents had the opportunity to formally teach mentees various high-yield IM topics. Program evaluation was completed using data from three participant cohorts, and showed that the program had a positive impact on students’ career decision making. Given the program’s flexible nature and ease of implementation, it is well suited for adaptation at other institutions.